Designing English Speaking Materials Based on EFL Students’ Learning Needs: A Needs Analysis at Vocational Schools - Sipayung, Kammer; Tampubolon, Sahlan; Pasaribu, Arsen Nahum; Fadhila, Fara; Zamorano, Alex (Journal of Language and Literature Studies, 2025)
The English Day program is an extracurricular program and an alternative process to improve students ability on speaking. English day able to amuse students and teacher to learn English.  The objectives of this research were to describe the students’ need for speaking materials and to design a Syllabus For the English Day Program at SMK Negeri 1 Satuatap.  The researchers used qualitative research design by using some instruments like questionnaires, observation, and interviews. The data of this study are information from these instruments; in other words, sources of data are the result of interviews, questionnaires, and observation.  The research respondents or sample of this study were 10 students, 10 teachers who guided the English Day Program, and 1 English Supervisor from the Education Department at Nias Barat to validate the syllabus design for the English Day Program. The findings showed that the students needed materials for speaking that were attractive and interesting, with a score 2,6 on the scale 1-4, and based on their daily and social life context, most students need speaking practice. The product of this study was a syllabus and supplementary speaking materials for the English Day Program. The contextual teaching and learning supplementary book consisted of three units. The result of the data computation of the book evaluation from the expert showed that the developed contextual teaching and learning speaking materials were categorized as good. The implication of this study, the English teacher must add more speaking practice in the English day materials.